Answer:
A. f(x) = 6x + 9
Step-by-step explanation:
The given equation is:
y - 6x - 9 = 0
We have to write this equation in function notation with x as the independent variable. This means that y will be replaced by f(x) and all other terms will be carried to the other side of the equation to get the desired function notation.
y - 6x - 9 = 0
y = 6x + 9
f(x) = 6x + 9
Therefore, option A gives the correct answer.
(0,0) is the cost of 0 bags of peanuts. This is because the x-axis is labeled "Bags of Peanuts", and an x-value of 0 implies 0 bags of peanuts.
Answer:
Step-by-step explanation:
3x+2y=12 x=
−2/
3
y+4
3x-y=3 x=
1
/3
y+1
i hope this helps in anyway :/
3 is to 5 as x is to 20
5 goes into 20 4 times so 3(4) gives you x
and x=12